In-situ transformation constructs CoTe/Co/CoO nanosheet arrays with rich grain boundaries to enhance electrochemical performance. (1st May 2022) - Chen, Mingyue; Lu, Yu; Li, Wenhui; Qi, Pengcheng; Liu, Gaofu; Wang, Shiyu; Chen, Zhigang; Tang, Yiwen
Abstract: Development of high conductivity and amorphous structure is at great significance in electrochemical storage applications. Two-dimensional nanosheet array has a large surface area and abundant active sites, showing great potential in the field of energy storage. Among many materials, Co-based oxides or hydroxides have high theoretical specific capacity and are widely used as electrode materials for hybrid supercapacitors, but low electrical conductivity inhibits their development. Here, Co(OH)2 nanosheet arrays are randomly transformed into CoTe, metallic Co, and CoO composite (CoTe/Co/CoO) during the hydrothermal process. The CoTe/Co/CoO nanosheets have abundant grain boundaries due to the multi-component effect. Thanks to the high elasticity of amorphous CoO, and the high conductivity of CoTe and Co, CoTe/Co/CoO composite nanosheet arrays exhibit excellent electrochemical performance, such as high capacity (501 C g −1 at 5 mA cm −2 ) and excellent cycle stability (95.2% capacity retention after 4000 cycles). Moreover, asymmetric supercapacitors are assembled with CoTe/Co/CoO as positive electrode and activated carbon as negative electrode, the developed device delivers a maximum energy density of 35.29 Wh Kg −1 with superb cycling stability.